QFD as a tool to improve negotiation process, product quality, and market success, in an automotive industry battery components supplier - Fonseca, Luís Miguel Ciravegna (2022)
30th International Conference on Flexible Automation and Intelligent Manufacturing (FAIM2021) 15-18 June 2021, Athens, Greece